Церковь Николая Великорецкого в Путивле - Чурочкин, А.А. (Сіверщина в історії України, 2018)
Статья посвящена уникальному памятнику народной архитектуры XVIII века – церкви Николая Великорецкого в Путивле. В научный оборот вводятся ранее не публиковавшиеся архивные материалы, раскрывающие некоторые факты истории храма XVIII–
ХХ вв., сделана попытка разобраться в путанице с названиями памятника. Стаття присвячена унікальній пам’ятці народної
архітектури XVIII століття – церкві Миколи Великоріцького у Путивлі. У науковий обіг вводяться архівні
матеріали, що раніше не публікувалися, які розкривають деякі факти історії храму XVIII–ХХ ст., зроблена
спроба розібратися в плутанині з назвами пам’ятника. The article is dedicated to the unique monument of folk
architecture of the XVIII century - the church of Nikolai
Velikoretsky in Putivl. The archival materials that were
previously unpublished, revealing some facts of the history
of the 18th-20th century church, are introduced into the
scientific circulation, an attempt to understand the confusion
with the names of the monument is made.